Validity and Reliability Assessment Tool of Nursing Students Professional Behavior - Fatikhu Yatuni Asmara (Universitas Airlangga, 2015)
Introduction: Shieffield Peer Review Assessment (SPRAT) is an instrument to assess medical student’s performance using Multi Source Feedback (MSF) method. The previous study stated that MSF with SPRAT is an effective tool assessing professional behaviour (PB) of nursing students both in clinical setting and community setting. However it needs more items to be added. Based on that explanation, it needs conducting validity and reliability test to make sure that the tool is valid and reliable.Method: There were two types of validity test used, content validity test and construct validity test as well as reliability test, namely inter-rater reliability test and item covariance test. Participants were four clinical instructors and 116 nursing students. Result: Content validity test showed that two items must be added as part of assessment item, namely diciplines and faithness. Furthermore construct validity test showed that five items were not valid since they had pearson correlation score <0.3. However the items were included as consideration of nursing students’s PB. Inter-rater reliability test and item covariance reliability test showed that the tool was reliable with score 0.460 and 0.912 respectively.Discussion: The assessment tool can be applied to assess PB of nursing students since it valid and reliable. It needs to investigate the effectiveness of the tool in difference of PB of nursing students.